The efficacy of an inactivated vaccine against pseudorabies in pigs and sheep - Lee, J. Y. S; Wilson, M. R; Povey, R. H. C. (Persatuan Doktor Veterinar Malaysia, 1979)
A formalin inactivated vaccine in an experimental adjuvant was shown to protect 95.5 percent of vaccinated pigs (8 - 13 weeks old when challenged against an intranasal challenge of 10 5.2-10 5.8 CCID 50 which killed 38.1 percent and induced clinical signs in 95 percent of control pigs. The vaccine also gave 83.3 percent protection in vaccinated sheep against intranasal challenge of 10 5.2 CCID50 while mortality ill control sheep was 100 percent.